Analisa Karakteristik Hujan di Kota Bandar Lampung - Margaretta Welly (UNIVERSITAS LAMPUNG, 2015)
Knowledge of the characteristics of rainfall causes floods and droughts is an important thing. This research intends to investigate the characteristics of rainfall in the city of Bandar Lampung in or- der to predict and anticipate events of drought and flood in Bandar Lampung. The data used in this study is the annual rainfall data obtained from four rainfall stations in Bandar Lampung from 1987 until 2006. The stations that are: Pahoman Station, Sukarame, Sumur Putri, and Kemiling (Sumber Rejo). The results showed that the pattern and trend of the respective data from each of the stations the rain is not too different from each other. Most of the stations showed decreased dy - namically on rainfall. Although this decline did not occur in the rest of the station, but in general decline is clearly visible when the trend was taken fourth. A dry year, the year in which the annual precipitation totals less than 90% of the average annual rainfall, dominated after the year 2000. Most of the rainfall in the year El Nino is below the average annual precipitation. Near Pahoman, there have been five times the annual rainfall is below average at the time of El Nino (1991, 1992, 1993, 2002, 2004). Near Sukarame, there has been four times the annual rainfall is below aver- age at the time of El Nino (1991, 1997, 2002, 2004). At the Sumur Putri station, there has been four times the annual rainfall is below average at the time of El Nino (1991, 1993, 2002, and 2004). Near Kemiling, there has been four times the annual rainfall is below average at the time of El Nino (1991, 1992, 1997, 2002). This suggests the possibility of EL Nino events are associ- ated with a decrease in rainfall in each station.